STRATIGRAPHIC TRAPS DELINEATION, SOUTHERN PATTANI BASIN, GULFOF THAILAND - Abdelaziz, Nesma (Bulletin of Earth Sciences of Thailand, 2021)
Pattani basin reservoirs has been heavily explored traditionally, focusing on structural traps. This study has been initiated to construct a new analogue model for identifying potential stratigraphic traps that have not been explored in the basin. Volumetric attributes have been used for data enhancement after a detailed analysis of the frequency spectrum. Spectral decomposition with RGB blending for three specified magnitudes has been used as a new method for random noise suppression and for stratigraphic imaging that is beyond seismic resolution. Detailed three-dimensional seismic interpretation and attributes analysis reveals that the potential stratigraphic traps at the eastern part of southern Pattani basin are an onlapping trap at unit two and truncation trap at unit one separated by an unconformity. The onlapping trap over a paleo-high area is formed because of basin subsidence and transgression phase. Stack of sand fill channels are observed within units three and four. These sands filled channels have been interpreted because of high sedimentation rates of South East Asia basins and because of transgressive sedimentation. A schematic model was constructed to understand the potential stratigraphic traps in the basin and can help in future exploration and well planning stages in Pattani basin.